2017
DOI: 10.3174/ajnr.a5139
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Variation in CT Parameters on Texture Features: Pilot Study Using a Nonanatomic Phantom

Abstract: Our aim was to evaluate changes in texture features based on variations in CT parameters on a phantom. Scans were performed with varying milliampere, kilovolt, section thickness, pitch, and acquisition mode. Forty-two texture features were extracted by using an in-house-developed Matlab program. Two-tailed tests and false-detection analyses were performed with significant differences in texture features based on detector array configurations ( values = 0.001-0.006), section thickness ( values = 0.0002-0.001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Original DICOM data sets were downloaded and then imported into in‐house developed MATLAB (MathWorks, Natick, MA) texture analysis software to calculate texture analysis features. The texture analysis software was developed by the co‐author (BL) and the use of this texture analysis program has been previously reported in the literature . Image segmentation of phantom was performed manually by an experienced radiologist (co‐author HK), using the same geometric boundaries and a uniform contour volume for each dataset in an effort to reduce potential variation related to the manual segmentation process.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Original DICOM data sets were downloaded and then imported into in‐house developed MATLAB (MathWorks, Natick, MA) texture analysis software to calculate texture analysis features. The texture analysis software was developed by the co‐author (BL) and the use of this texture analysis program has been previously reported in the literature . Image segmentation of phantom was performed manually by an experienced radiologist (co‐author HK), using the same geometric boundaries and a uniform contour volume for each dataset in an effort to reduce potential variation related to the manual segmentation process.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous texture analysis equations have been defined and developed. Only a subset of 41 texture features were employed in this study based on our prior work, and based on the popularity of reported texture features in the radiomics literature …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations